Influence of ohmic heating on the structural and immunoreactive properties of soybean proteins - Pereira, Ricardo N. (2021)
Ohmic heating (OH) encompasses interesting benefits towards thermal processing. Envisaging an increasing relevance of soybean protein as an alternative non-animal protein, it is important to understand how OH can contribute to the quality and immunoreactivity of soybean-derived products. This study describes, for the first time, the impact of OH when applied at different electrical frequencies (50 Hz20 kHz) and moderate electric field intensities (up to 20 V/cm), on the leakage of metals from the electrodes and immunoreactivity aspects of soybean protein isolate (SPI). This was achieved by monitoring the occurrence of electrochemical reactions and evaluating IgG-binding capacity. OH performed at 50 Hz and 95 °C induced significant alterations on the intrinsic fluorescence of SPI (p  0.05) and the release of detectable amounts of Fe/Ni, with a subsequent reduction of 36% in the immunoreactivity of Gly m TI. The occurrence of non-thermal effects, as well as the interaction between protein and trace metals, may result in a partial blockage of protein epitopes, thus impairing specific antibody binding. These findings present novel information about the importance of OH parameters, such as electrical frequency and occurrence of electrochemical reactions, which can affect the structure and immunoreactivity of SPI fractions.